Evaluation of occurrence of sesamoid bones in the lower extremity radiographs - Ghimire, Indu; Maharjan, Surendra; Pokharel, Ganesh Bahadur; Subedi, Kamal (Journal of Chitwan Medical College, 2017)
The purpose of this study was to examine the plain AP radiograph of foot and lateral radiograph of knee in order to determine the prevalence and size of sesamoid bone in different part of foot and on the posterior aspect of the knee joint. A cross-sectional study was performed in Department of Radiology and Imaging, Tribhuvan University Teaching Hospital from July to September 2014. A total of 206 radiographs of foot (55) and knee (155) were collected. 121 (58.7%) were female and 85 (41.3%) were male. The most common site of sesamoid bone in foot was in the first metatarsal joint (96.4%) whereas the sesamoid bone in knee joint, fabella was found in 12.3% of total cases. The prevalence is more common in female than in male. The length and breadth of the sesamoid bones were measured and then area of bones was calculated. The size of medial and lateral sesamoid bone in the first MTP Joint was measured 0.6225 cm2 and 0.8261 cm2 respectively. The mean size of sesamoid bone of knee, fabella was 0.2818 cm2.